An Immune-Related Gene Prognostic Index for Head and Neck Squamous Cell Carcinoma - Chen, Yue; Li, Zhi-Yong; Zhou, Guan-Qun; Sun, Ying (Clinical cancer research, 2021)
To construct an immune-related gene prognostic index (IRGPI) for head and neck squamous cell carcinoma (HNSCC) and clarify the molecular and immune characteristics and the benefit of immune checkpoint inhibitor (ICI) therapy in IRGPI-defined subgroups of HNSCC. On the basis of The Cancer Genome Atlas HNSCC immune dataset ( = 546), 22 immune-related hub genes were identified by weighted gene coexpression network analysis. Three genes were identified to construct an IRGPI by using the Cox regression method and validated with the Gene Expression Omnibus (GEO) dataset ( = 270). Afterward, the molecular and immune characteristics and the benefit of ICI therapy in IRGPI-defined subgroups were analyzed. The IRGPI was constructed on the basis of , , and genes. IRGPI-high patients had a better overall survival than IRGPI-low patients, consistent with the results in the GEO cohort. The comprehensive results showed that a high IRGPI score was correlated with DNA repair-related pathways; low mutation rate; high infiltration of CD8 T cells, CD4 T cells, and M1 macrophages; active immunity and less aggressive phenotypes; and more benefit from ICI therapy. In contrast, a low IRGPI score was associated with cancer and metastasis-related pathways; high and mutation rate; high infiltration of B cells, M0 macrophages, and M2 macrophages; suppressive immunity and more aggressive phenotypes; and less benefit from ICI therapy. IRGPI is a promising biomarker to distinguish the prognosis, the molecular and immune characteristics, and the immune benefit from ICI therapy in HNSCC.